2018
DOI: 10.1002/csr.1496
|View full text |Cite
|
Sign up to set email alerts
|

Environmental policy disclosures and sustainable development: Determinants, measure and impact on firm value for ADX listed companies

Abstract: Corporate social responsibility (CSR) disclosures have gained great attention in both the media and the academic community for many decades. In this paper, we shed light on three aspects of CSR disclosures, namely the determinants, measure and impact on firm value. Using a sample of 61 firms listed on the ADX for the period 2010-2014 and computing an eight-item index, our results are conclusive and show that listing history, governmental sector, board size, financial leverage and firm size have a positive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 63 publications
7
46
2
3
Order By: Relevance
“…Hence, high financial leverage will encourage firms to disclose more environmental information. The results of several studies provide support for this expectation (Clarkson et al, 2008;Huang & Kung, 2010;Zeng et al, 2012;Guidry & Patten, 2012;Juhmani, 2014;Sulaiman et al, 2014;Yildiz et al, 2016;Ismail et al, 2018;Kolsi & Attayah, 2018). Accordingly, we state the following hypothesis:…”
Section: Financial Leveragesupporting
confidence: 60%
See 1 more Smart Citation
“…Hence, high financial leverage will encourage firms to disclose more environmental information. The results of several studies provide support for this expectation (Clarkson et al, 2008;Huang & Kung, 2010;Zeng et al, 2012;Guidry & Patten, 2012;Juhmani, 2014;Sulaiman et al, 2014;Yildiz et al, 2016;Ismail et al, 2018;Kolsi & Attayah, 2018). Accordingly, we state the following hypothesis:…”
Section: Financial Leveragesupporting
confidence: 60%
“…Hackston & Milne, 1996;Patten, 2002;Brammer & Pavelin, 2006;Liu & Anbumozhi, 2009;Huang & Kung, 2010;Wang et al, 2012;Lu, 2014;Akbaş, 2014;Fontana et al, 2015;Welbeck et al, 2017;Ismail et al, 2018;Ofoegbu et al, 2018;Ashfaq & Rui, 2019). However, some studies reported an insignificant relation between industry type and environmental disclosure (Braam et al, 2016;Ahmadi & Bouri, 2017;Kolsi & Attayah, 2018;Kılıç & Kuzey, 2019;Akbaş & Canikli, 2019;Kouloukoui et al, 2019).…”
Section: Industry Typementioning
confidence: 99%
“…checklist, counting words and sentences (Appuhami & Tashakor, 2017;Barakat et al, 2015;Jizi et al, 2014;Khan et al, 2013;Kolsi & Attayah, 2018;Sharif & Rashid, 2014;Zaid et al, 2019). Other studies measure CSRD using ESG rating depending on Bloomberg database (Al-Dah et al, 2018;Cucari et al, 2018;Giannarakis et al, 2014), and by using KPMG international surveys of CSR reporting (Fernandez-Feijoo et al, 2014), using a dummy variable (Liao et al, 2018;Pucheta-Martinez & Chiva-Ortells, 2018), Dow Jones Sustainability Indices (Chang et al, 2017), and GRI database (Cabeza-Garcia et al, 2018;Fuente et al, 2017).…”
Section: Study Objective 4: Most Relevant Topics In the Literaturementioning
confidence: 99%
“…In addition, we provide empirical confirmation that implementation of the GRI‐IFC disclosure strategy is associated with greater accuracy in analysts' forecasts. This new information communication strategy could overcome the lack of investor confidence in CSR reports that has been referred to in previous research (Carnevale et al, ; Kolsi & Attayah, ; Murray et al, ; Solomon & Solomon, ) and reinforce the usefulness of the CSR disclosure items that represent the company's commitment to its stakeholders (Brown‐Liburd & Zamora, ).…”
Section: Resultsmentioning
confidence: 89%
“…However, several authors have commented that CSR reporting does not necessarily provide useful information for shareholders (Carnevale et al, ; Kolsi & Attayah, ; Murray et al, ; Solomon & Solomon, ). In this vein, García‐Sánchez and Noguera‐Gámez (, ) observed that key financial and nonfinancial information should be published in order to reduce information asymmetry and to support confidence among investors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%